Increased sputum lactate during oral glucose tolerance test in cystic fibrosis. Issue 8 (30th May 2022) - Jensen, Peter Østrup; Nielsen, Bibi Uhre; Kolpen, Mette; Pressler, Tacjana; Faurholt‐Jepsen, Daniel; Mathiesen, Inger Hee Mabuza
Abstract : Blood glucose levels exceeding 8 mM are shown to increase glucose levels in airway surface in cystic fibrosis (CF). Moreover, high levels of endobronchial glucose are proposed to increase the growth of common CF bacteria and feed the neutrophil‐driven inflammation. In the infected airways, glucose may be metabolized by glycolysis to lactate by both bacteria and neutrophils. Therefore, we aimed to investigate whether increased blood glucose may fuel the glycolytic pathways of the lung inflammation by determining sputum glucose and lactate during an oral glucose tolerance test (OGTT). Sputum from 27 CF patients was collected during an OGTT. Sputum was collected at fasting and one and two hours following the intake of 75 g of glucose. Only participants able to expectorate more than one sputum sample were included. Glucose levels in venous blood and lactate and glucose content in sputum were analyzed using a regular blood gas analyzer. We collected 62 sputum samples: 20 at baseline, 22 after 1 h, and 20 after 2 h. Lactate and glucose were detectable in 30 (48.4%) and 43 (69.4%) sputum samples, respectively. The sputum lactate increased significantly at 2 h in the OGTT (p = 0.024), but sputum glucose was not changed. As expected, plasma glucose level significantly increased during the OGTT (p < 0.001). In CF patients, sputum lactate increased during an OGTT, while the sputum glucose did not reflect the increased plasma glucose. The increase in sputum lactate suggests that glucose spills over from plasma to sputum where glucose may enhance the inflammation by fueling the anaerobic metabolism in neutrophils or bacteria.